Chronic skin disease and levels of physical activity in 17 777 Spanish adults: a cross‐sectional study. (1st April 2021) - Jacob, L.; López‐Sánchez, G. F.; Koyanagi, A.; Veronese, N.; Vioque‐López, J.; Oh, H.; Shin, J. I.; Schnitzler, A.; Ilie, C. P.; Stefanescu, S.; Gillvray, C.; Machado, M. O.; et al.
Abstract: Background: To date there is limited literature on the prevalence of chronic skin conditions and its association with levels of physical activity (PA) in Spain. Aim: To determine the prevalence of chronic skin disease and to compare levels of PA between people with and without chronic skin disease in a large representative sample of Spanish adults aged 15–69 years. Methods: Data from the Spanish National Health Survey 2017 were analysed. Chronic skin disease was assessed using a yes/no question. PA was measured using the short form of the International Physical Activity Questionnaire. Total PA metabolic equivalent of task min/week were calculated, and PA was included in the analyses as a continuous and a five‐category variable. Results: This cross‐sectional study included 17 777 adult participants (52.0% women; mean ± SD age 45.8 ± 14.1 years), of whom 940 (5.3%) had chronic skin disease. After adjusting for several potential confounders, there was a negative association between chronic skin disease and PA (OR = 0.87, 95% CI 0.76–1.00, P = 0.05), which was significant for men (OR = 0.76, 95% CI 0.62–0.93, P = 0.01) but not for women (OR = 0.97, 95% CI 0.81–1.16, P = 0.72). Conclusions: In this large representative sample of Spanish adults, the prevalence of chronic skin disease was low. Levels of PA were lower in men with than in men without chronic skin conditions, but this association was not seen in women.